2020
DOI: 10.1007/s13300-020-00913-y
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Injection Practices in a Population of Canadians with Diabetes: An Observational Study

Abstract: Introduction: Proper insulin injection technique has demonstrated positive clinical outcomes in patients with diabetes. A Canadianbased practice reflective was undertaken to evaluate the current state of understanding of injection technique practices by patients administering insulin, and the importance physicians place on proper injection technique. Methods: Twenty-four sites across Canada completed a practice profile survey and enrolled adult non-pregnant patients with either type 1 or type 2 diabetes inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 41 publications
3
14
1
Order By: Relevance
“…Consistent with the literature [ 29 , 30 ], this study found that patients skipped all aspects of priming insulin pen before injection, which could affect the effectiveness of needle and the existence of air bubbles. It has also been suggested to keep the needle under the skin in 6 to 10 seconds before withdrawal to ensure full absorption of insulin, but this practice was found only in around one-third of patients in our study, which is lower than Bari et al (39%) and Poudel et al (53.5%) [ 29 , 30 ]. Errors in the insulin injection technique also included not removing the needle cap and used needle from pen after injection (90%) and not mixing cloudy insulin (51.2%).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with the literature [ 29 , 30 ], this study found that patients skipped all aspects of priming insulin pen before injection, which could affect the effectiveness of needle and the existence of air bubbles. It has also been suggested to keep the needle under the skin in 6 to 10 seconds before withdrawal to ensure full absorption of insulin, but this practice was found only in around one-third of patients in our study, which is lower than Bari et al (39%) and Poudel et al (53.5%) [ 29 , 30 ]. Errors in the insulin injection technique also included not removing the needle cap and used needle from pen after injection (90%) and not mixing cloudy insulin (51.2%).…”
Section: Discussionsupporting
confidence: 88%
“…Several studies had described that patient preference and satisfaction on the use of insulin pen devices lead to increased patient compliance. [32][33][34] Educators should inform subsequently standardized guidance around insulin including injection sites and method. Incorrect knowledge about insulin injections, for example, needle reuse, of patients with diabetes may lead to lipohypertrophy in the injection area, which increase hypoglycemia risk.…”
mentioning
confidence: 99%
“…Incorrect knowledge about insulin injections, for example, needle reuse, of patients with diabetes may lead to lipohypertrophy in the injection area, which increase hypoglycemia risk. [34][35][36][37][38][39] The majority of AEs in the present study were mild. There were four events of SAEs in the EZL group and seven SAEs in the LAN group.…”
mentioning
confidence: 99%
“…51 Many participants reported using a smaller than recommended area for their insulin injections (64%), reusing their PNs (39%), or injecting into lipohypertrophic tissue (lumps or bumps under their skin; 37%). 51 Lipohypertrophy (LH) is a common complication of insulin injections in people with diabetes (both type 1 and type 2), with reported prevalence ranging from 30 to 65% depending on study population. 30,52,53 Predisposing factors for LH development that have been described include small skin area size in which injections are applied repeatedly, failure to rotate injection sites, needle reuse, low BMI (underweight), and use of ice-cold insulin.…”
Section: Injection Technique Educationmentioning
confidence: 99%